Evaluación de la vida útil de la zanahoria aplicando tres desinfectantes diferentes, en la parroquia Chuquiribamba, cantón y provincia de Loja - Rojas Paccha, Verónica Cristina (2020)
The disinfection constitutes a very important factor to ensure the quality and safety of the food for the human consumption, for it several agents exist disinfectants capable of diminishing the effect of the factors of deterioration and with it to lengthen the time of useful life. The present thesis project was as a purpose to evaluate the quality of the carrot cut in little cubes and disinfected by means of the application of three types of disinfectants; for it preliminary tests were realized with four disinfectants to different concentrations (hipoclorito of sodium 50,100 and 150 ppm; ozone to 20 and 40 ppm; essential oil of oregano and thyme to 20, 30 and 40 ppm), then to establish three definitive treatments (hipoclorito of sodium to 100 ppm – T2, ozone to 40 ppm – T3 and essential oregano oil to 30 ppm - T4), to which the quality was evaluated by means of the changes organolépticos, physicist - chemist and microbiological during the storage time. The results show that in all the quality characteristics of the product there exist significant differences between the treatment witness (T1) and other (T2, T3 and T4). In the latter it is observed that there are no statistically significant differences in the chemical composition and organoleptic attributes (color, flavor and texture); however, the storage time was 28 days for T2 and T3, while for T4 he was 35 days old; as for the load microbiana it is observed that the T4 they contain the least quantity of coliformes, molds and yeasts and absence of E. coli. With which it is concluded that treatment 4 presented a longer useful life, the disinfection parameters were: the type disinfectant is the essential oregano oil, the concentration is 30 ppm and the time of immersion of the product is 5 minutes; finally, the variable production costs to prepare 227 grams of this product, it is to 0,30 USD with a retail price of 0,40 USD considering 30 % of utility.